NaV1.7 and pain: contribution of peripheral nerves - Hoffmann, Tal; Carr, Richard (Pain, 2018)
The sodium channel NaV1.7 contributes to action potential (AP) generation and propagation. Loss-of-function mutations in patients lead to congenital indifference to pain, though it remains unclear where on the way from sensory terminals to central nervous system the signalling is disrupted. We confirm that conditional deletion of NaV1.7 in advillin-expressing sensory neurons leads to impaired heat and mechanical nociception in behavioural tests. With single-fiber recordings from isolated skin, we found (1) a significantly lower prevalence of heat responsiveness to normally mechanosensitive C-fibers, although (2) the rare heat responses seemed quite vigorous, and (3) heat-induced calcitonin gene-related peptide release was normal. In biophysical respects, although electrical excitability, rheobase, and chronaxy were normal, (4) axonal conduction velocity was 20% slower than in congenic wild-type mice (5) and when challenged with double pulses (<100 milliseconds interval), the second AP showed more pronounced latency increase (6). On prolonged electrical stimulation at 2 Hz, (7) activity-dependent slowing of nerve fiber conduction was markedly less, and (8) was less likely to result in conduction failure of the mutant single fibers. Finally, recording of compound APs from the whole saphenous nerve confirmed slower conduction and less activity-dependent slowing as well as the functional absence of a large subpopulation of C-fibers (9) in conditional NaV1.7Adv knockouts. In conclusion, the clear deficits in somatic primary afferent functions shown in our study may be complemented by previously reported synaptic dysfunction and opioidergic inhibition, together accounting for the complete insensitivity to pain in the human mutants lacking NaV1.7.
Gesehen am 16.06.2020